Evidence for paternal imprinting in familial Beckwith-Wiedemann syndrome. - Viljoen, D (1992)
A previously unreported family in which seven members in two generations have Beckwith-Wiedemann syndrome (BWS) is documented. Paternal imprinting of the gene responsible for BWS is involved as the mechanism responsible for the aberrant inheritance pattern in this kindred. A review of published reports showed 27 previously published pedigrees with two or more affected subjects with BWS. Paternal imprinting would explain the non-mendelian inheritance of BWS in all but four kindreds. The latter families are examined in more detail and in only one example is the evidence against imprinting totally unexplained.